Sliding to the rescue of damaged DNA - Bryan Gibb; Eric C Greene (eLife, 2012)
Single-molecule imaging experiments have shed new light on the methods used by the enzyme RecA to align single- and double-stranded DNA so that double-strand breaks can be repaired.